Penanggulangan Perdagangan Orang di Kawasan Asean: Pendekatan Hukum dan Tantangan Implementasi - Khilda Nur Azizah; Sultan Maulana Adrian; Zaenuddin (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Human trafficking, or human trafficking, is one of the most serious forms of transnational crime globally and in Southeast Asia. ASEAN, as a regional organization, has issued legal instruments and shared working mechanisms to address this phenomenon, particularly through the 2015 ASEAN Convention Against Trafficking in Persons, Especially Women and Children (ACTIP) and additional guidelines related to the principle of non-punishment for victim protection. However, implementation of the law at the national level still faces various challenges due to differences in legal systems, enforcement capacity, and the ASEAN Way approach. This article discusses the ASEAN and national legal frameworks for combating human trafficking and the challenges in their implementation. Keywords: Human Trafficking, ASEAN, ACTIP, Law Enforcement, Victim Protection. Abstrak Perdagangan orang atau trafficking in persons merupakan salah satu bentuk kejahatan transnasional yang paling serius di dunia dan di kawasan Asia Tenggara. ASEAN sebagai organisasi regional telah mengeluarkan instrumen hukum dan mekanisme kerja sama untuk menanggulangi fenomena tersebut, terutama melalui ASEAN Convention Against Trafficking in Persons, Especially Women and Children (ACTIP) 2015 dan pedoman tambahan terkait prinsip non-punishment untuk perlindungan korban. Namun, implementasi hukum di tingkat nasional masih menghadapi berbagai tantangan karena perbedaan sistem hukum, kapasitas penegakan, dan pendekatan ASEAN Way. Artikel ini menganalisis kerangka hukum ASEAN dan nasional dalam menanggulangi perdagangan orang, serta tantangan dalam implementasinya. Kata kunci: Perdagangan Orang, ASEAN, ACTIP, Penegakan Hukum, Perlindungan Korban